PROMIS Physical and Emotional Health Scores Are Worse in Musculoskeletal Patients Presenting to Physiatrists than to Other Orthopedic Specialists. Issue 6 (25th March 2019) - Cheng, Abby L.; Calfee, Ryan; Colditz, Graham; Prather, Heidi
Abstract : Background: Physiatrists' unique training in person‐centered biopsychosocial management of complex problems may influence musculoskeletal patients' expectations and self‐ and/or physician‐referral patterns to physiatrists. Consequently, average patient complexity and need for multi‐disciplinary services may be increased in physiatric patients. Objective: To compare musculoskeletal patients' self‐reported physical and emotional health according to provider specialty. Researchers tested the null hypothesis that there is no significant difference in Patient‐Reported Outcomes Measurement Information System (PROMIS) scores between patients who present to physiatrists in comparison to other musculoskeletal specialists. Design: Cross‐sectional study. Setting: Orthopedic department of a tertiary academic medical center. Patients: Participants included 31 791 new adult patients (mean age 52.6 ± 16.2 years) who presented for initial elective evaluation of a musculoskeletal problem by an orthopedic surgeon or sports medicine trained emergency medicine, family medicine, pediatric, or physiatric physician. Methods: Patients completed the PROMIS computer adaptive test (CAT) Physical Function, Pain Interference, Anxiety, and Depression domains at department check‐in prior to the physician encounter. Score differences by provider type were assessed using Wilcoxon rank‐sum tests. Main Outcome Measurements: Mean PROMIS score in each domain subdivided by physiatric, surgical, and other nonsurgical provider type. Results: In total, 2081 patients presented to physiatrists, 28 267 presented to surgeons, and 1443 presented to other nonsurgical providers. For each respective provider type, average PROMIS scores were Physical Function 38.9 ± 8.2, 41.5 ± 9.5, and 43.5 ± 8.2; Pain Interference 62.6 ± 7.2, 60.9 ± 7.7, and 59.2 ± 6.8; Anxiety 54.5 ± 10.4, 51.9 ± 10.6, and 49.8 ± 9.8; and Depression 49.3 ± 10.4, 47.0 ± 10.0, and 44.2 ± 8.7. Physiatric patients had significantly worse average scores for all domains compared to surgical ( P < .001) and other nonsurgical patients ( P < .001). Conclusions: Average PROMIS Physical Function, Pain Interference, Anxiety, and Depression scores were worse in musculoskeletal patients who presented to physiatrists in comparison to surgical or other nonsurgical providers. This suggests that some patients who choose to see or are referred to see physiatrists may have more or be more willing to endorse having biopsychosocial impairments. Level of Evidence: III